2011
DOI: 10.1108/09590551111133394
|View full text |Cite
|
Sign up to set email alerts
|

An empirical multi‐method investigation of price knowledge in food retailing

Abstract: PurposeThis paper aims to add insights on consumers' price knowledge in food retailing using a theory‐based multi‐method approach.Design/methodology/approachThe paper provides data from one questionnaire and two experimental studies. The aim of the first study was to address price recall. To do so, data were collected on the accuracy of grocery‐shopper price knowledge for 20 carefully selected products. Using the mall intercept method, three trained interviewers queried 300 randomly selected people in the stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
2
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 50 publications
0
9
2
3
Order By: Relevance
“…In terms of price, the results of this study indicate that a very competitive price influences consumer's decision (Kenning et al, 2011). The positive and significant impact of this study can be interpreted: if price matches the quality, it will improve buying decisions.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…In terms of price, the results of this study indicate that a very competitive price influences consumer's decision (Kenning et al, 2011). The positive and significant impact of this study can be interpreted: if price matches the quality, it will improve buying decisions.…”
Section: Discussionmentioning
confidence: 61%
“…Price is an element that generates revenue for producers of goods (Monroe, 2002;Kenning et al, 2011). According to Eberhardt et al (2009), price is the amount of money charged for the product or service purchased by customers.…”
Section: Price and Buying Decisionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that this procedure does not reduce the accuracy of the responses(Kenning, Hartleb, & Schneider, 2011).3 This study is based on a sample first reported inRampl and Kenning (2014). The paper byRampl and Kenning (2014) had a different scope than the one reported here, and out of the eight scales investigated in this present work, only one scale (the employer brand emotions scale) was also part of theRampl and Kenning (2014) publication.…”
mentioning
confidence: 83%
“…In terms of price-related information, there is compelling evidence that shoppers expend resources to obtain and process price information both across and within stores (Putrevu & Lord, 2001;Urbany et al, 1996;Urbany, Dickson, & Sawyer, 2000). Importantly, however, it has been well documented that shoppers have poor grocery price knowledge and recall (Dickson & Sawyer, 1990;Kenning, Hartleb, & Schneider, 2011;Pechtl, 2008). Nevertheless, it is clear that price information gathered helps determine the shopper's reference price and influences the purchase decision, and this results in conscious search processes for the 'best deals' (Briesch, Krishnamurthi, Mazumdar, & Raj, 1997;Monroe, 1973;Vanhuele & Drèze, 2002).…”
Section: Information Searchmentioning
confidence: 93%